2018
DOI: 10.2147/btt.s168691
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of drug utilization and health care resource consumption in patients with psoriasis and psoriatic arthritis before and after treatment with biological therapies

Abstract: ObjectivesTo describe the therapeutic pathways of patients with psoriasis (PSO) and psoriatic arthritis (PsA) before and after treatment with biological therapies in a real-world setting and to determine the relative consumption of health care resources.DesignRetrospective observational study.SettingReal-life clinical setting in 5 Italian local health units.ParticipantsA total of 351 male and female patients with at least 1 prescription for a biological drug from January 1, 2010 to December 31, 2013; patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
12
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
7
12
1
2
Order By: Relevance
“…A higher proportion of the PsA patients (32.2%) were treated with bDMARDs (mostly with etanercept and adalimumab) compared to the PsO patients (4.9%), in which ustekinumab was the most frequently used bDMARD. Compared with a previous drug utilization study conducted in Italian PsO and PsA patients [ 31 ], etanercept, adalimumab and ustekinumab were the three most frequently reported bDMARDs as the first biological treatment; however, the proportion of PsO and PsA patients treated with these compounds was higher, except for ustekinumab in PsA, compared to our study. Furthermore, Marcianò et al documented, using the claims database, an underutilization of bDMARDs in PsO/PsA patients from another general population of Southern Italy in the years 2010–2014 [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 96%
“…A higher proportion of the PsA patients (32.2%) were treated with bDMARDs (mostly with etanercept and adalimumab) compared to the PsO patients (4.9%), in which ustekinumab was the most frequently used bDMARD. Compared with a previous drug utilization study conducted in Italian PsO and PsA patients [ 31 ], etanercept, adalimumab and ustekinumab were the three most frequently reported bDMARDs as the first biological treatment; however, the proportion of PsO and PsA patients treated with these compounds was higher, except for ustekinumab in PsA, compared to our study. Furthermore, Marcianò et al documented, using the claims database, an underutilization of bDMARDs in PsO/PsA patients from another general population of Southern Italy in the years 2010–2014 [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 96%
“…Основные затраты при оказании медицинской помощи по поводу псориаза связаны с ее оказанием в стационарах как дневных, так и круглосуточных [21,22]. Однако исследования показателей госпитализации пациентов с псориазом в период после появления биологических генно-инженерных препаратов ограничены, а их результаты противоречивы.…”
Section: %unclassified
“…Однако исследования показателей госпитализации пациентов с псориазом в период после появления биологических генно-инженерных препаратов ограничены, а их результаты противоречивы. Некоторые авторы констатируют снижение потребности в госпитализации как по поводу псориаза, так и по поводу ассоциированных с псориазом состояний после появления биологических генно-инженерных препаратов [21]. Другие исследователи указывают на отсутствие изменений и тенденцию к росту количества госпитализаций по поводу обострений псориаза после появления биологических генно-инженерных препаратов и предполагают, что это может быть связано как с ростом заболеваемости, так и с осведомленностью пациентов о появлении нового эффективного лекарственного лечения и повышением вследствие этого обращаемости за медицинской помощью [23].…”
Section: %unclassified
“…As a systemic inflammatory disease, psoriasis is plagued by comorbidities, including psoriatic arthritis and cardiovascular diseases that may reduce life expectancy . Interestingly, recently Mehta's group showed that treatment with biologics could reduce coronary inflammation and healthcare resource consumption . Furthermore, duration of skin lesions has been linked to the risk of PsA, hypothesizing that early and aggressive intervention may prevent the development of PsA, and perhaps other comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…22 Interestingly, recently Mehta's group showed that treatment with biologics could reduce coronary inflammation and healthcare resource consumption. 23,24 Furthermore, duration of skin lesions has been linked to the risk of PsA, hypothesizing that early and aggressive intervention may prevent the development of PsA, 25 and perhaps other comorbidities. Moreover, we should also pay attention to the Cumulative Life Course Impairment that patients with psoriasis experience, including a heavy burden on their social and mental well-being over several years living with the disease.…”
Section: Introductionmentioning
confidence: 99%